COMPARATIVE ANALYSIS OF COLUMN AND BEAMS VOLUMES OF CONVENTIONAL STRUCTURES WITH OUTPUT FROM AUTODESK REVIT AND PLAN TIME WITH WORK REALIZATION USING NAVISWORK - Ariany Frederika; A.A Gde Agung Yana; I G. A. Adnyana Putera; Muhammad Risqi A (Jurnal Ilmiah Teknik Sipil, 2024)
The government issued regulations related to BIM (Building Information Modeling) in July 2021. The PUPR Ministry issued circular no. 11/SE/Db/2021 which requires the implementation of BIM. There are BIM supporting applications, namely Autodesk Revit andAutodesk Naviswork. This research takes a case study of the construction of the Prof. Mother and Child Hospital Building. Dr. I.G.N.G Ngoerah Denpasar, whose BoQ calculations still use conventional or manual methods. Therefore, this research was carried out to find out the comparison of the Building Information Modeling and conventional concepts. Secondary data includes work drawings, BoQ, schedule and AHSP. Based on the research that has been carried out, the results of the comparison of the volume of columns and beams of the Autodesk Revit output structure are the total volume of 852,921.74 kg of steel and 2,456.72 m3 of concrete with a comparison of the volume of concrete between conventional and output from Autodesk Revit 1:0.946 and the volume ratio of 1:0.976 with a total cost of conventional RAB of IDR 19,313,295,875.58 and RAB from Autodesk Revit of IDR 18,760,742,153.46 with a ratio ofconventional RAB to output from Autodesk Revit of 1:0.971. deviation of -2.95% where the RAB from Autodesk Revit is IDR 552,553,722.12 less. The results of the plan time display with realization produce 12 work items that are being worked on and 30% work realization is achieved on day 119.